Evidence that Xrn1 is in complex with Gcn1, and is required for full levels of eIF2α phosphorylation - Shanmugam R; Anderson R; Schiemann AH; Sattlegger E (Portland Press on behalf of the Biochemical Society, 2024)
The protein kinase Gcn2 and its effector protein Gcn1 are part of the General Amino Acid Control signalling (GAAC) pathway best known in yeast for its function in maintaining amino acid homeostasis.  Under amino acid limitation, Gcn2 becomes activated, subsequently increasing the levels of phosphorylated eIF2α (eIF2α-P).  This leads to the increased translation of transcriptional regulators, such as Gcn4 in yeast and ATF4 in mammals, and subsequent re-programming of the cell's gene transcription profile, thereby allowing cells to cope with starvation.  Xrn1 is involved in RNA decay, quality control and processing.  We found that Xrn1 co-precipitates Gcn1 and Gcn2, suggesting that these three proteins are in the same complex.  Growth under starvation conditions was dependent on Xrn1 but not on Xrn1-ribosome association, and this correlated with reduced eIF2α-P levels.  Constitutively active Gcn2 leads to a growth defect due to eIF2α-hyperphosphorylation, and we found that this phenotype was independent of Xrn1, suggesting that xrn1 deletion doesn't enhance eIF2α de-phosphorylation.  Our study provides evidence that Xrn1 is required for efficient Gcn2 activation, directly or indirectly.  Thus, we have uncovered a potential new link between RNA metabolism and the GAAC.
Keywords: Gcn1; Gcn2; Molecular Biology; Sacharomyces cerevisiae; Xrn1; starvation signaling